Abundance estimation with a categorical covariate subject to missing in continuous-time capture-recapture studies - Liu, Yang; Zhu, Lin; Liu, Guanfu; Li, Huapeng (Communications in statistics. Theory and methods, 2020)
In continuous-time capture-recapture experiments, individual heterogeneity has a large effect on the capture probability. To account for the heterogeneity, we consider an individual covariate, which is categorical and subject to missing. In this article, we develop a general model to summarize three kinds of missing mechanisms, and propose a maximum likelihood estimator of the abundance. A likelihood ratio confidence interval of the abundance is also proposed. We illustrate the proposed methods by simulation studies and a real data example of a bird species prinia subflava in Hong Kong.